(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: Since reward and incentive programs play a key role in attracting new employees and motivating existing ones, we decided to investigate which programs are used by highly desirable employers and how satisfied their employees are with these programs. Methodology: A survey on employee satisfaction with work and reward and incentive programs was conducted among 160 (10%) employees of the company dm-drogerie markt d.o.o. The obtained data were processed using methods of descriptive statistics and non-parametric tests. Results: The average satisfaction of employees with the reward and incentive system is 4.39 on a scale from 1 to 5, where 5 means “completely satisfied”. The average job satisfaction is 4.47, and a moderate positive correlation was found between job satisfaction and satisfaction with the reward and incentive system (rs=0.523, p<0.010). Differences in the level of satisfaction were found in relation to the department and salary level of the respondents: more satisfaction was expressed by employees in the Sales Region department and by those in the highest salary level. Conclusion: The analysis revealed a high average satisfaction level, but also a gap between the importance that employees attach to a particular program and their satisfaction with that program. The results confirm the importance of the reward and incentive system for overall job satisfaction and can be used to improve this system within the company.